Investigating genomic diversity of Staphylococcus aureus associated with pediatric atopic dermatitis in South Africa - Ndhlovu, Gillian O. N.; Javkar, Kiran G.; Matuvhunye, Takudzwa; Ngondoh, Froodia; Jamrozy, Dorota; Bentley, Stephen; Shittu, Adebayo O.; Dube, Felix S. (Frontiers in Microbiology, 2024)
Importance: Staphylococcus aureus frequently colonises the skin and nose of patients with atopic dermatitis (AD), a disease associated with skin barrier dysfunction and chronic cutaneous inflammation. Published genomic studies on AD-associated S. aureus in paediatric populations in sub-Saharan Africa are limited. Objectives: To investigate the phenotypic and genomic diversity of S. aureus in children with and without AD during early childhood. Data, setting and participants: A cross-sectional study of 220 children (aged 9-38 months) with AD (cases) and without AD (controls) from Cape Town and Umtata, South Africa.Main outcomes and measures: S. aureus phenotypic and genomic diversity were investigated using whole-genome sequencing, antibiotic susceptibility testing and biofilm microtiter assay.Of the 124 S. aureus isolates recovered from 220 children, 96 isolates (79 cases and 17 controls) with high-quality sequences were analysed. Isolates from cases showed greater phenotypic resistance to gentamicin (10%), rifampicin (4%), chloramphenicol (4%), and exhibited multidrug resistance (9%) than in controls. Furthermore, the isolates from cases formed stronger biofilms than those from controls (76% vs. 35%, p=0.001), but showed no dominance of any virulence factor gene or mobile genetic elements. There was no significant difference in the distribution of immune evasion cluster types between cases and controls. However, IEC type G was identified only among cases.AD-associated S. aureus has phenotypic and genetic features that are important for successful pathogenic colonisation and survival. Further studies are needed to assess the pathological implications of colonisation of various S. aureus lineages in vivo to elucidate their pathological contribution to AD pathogenesis and pathophysiology.